Situation Report: Hungary, 10 September 1974 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. World Congress of Economists in Budapest Developing Domestic Trade - A Precondition for Raising the Living Standard More Inexpensive Radio and TV Sets Needed Machinery Imported from the West Speeds Fall Work Too Few Skilled Workers in the Farmers' Cooperatives